Does sustainability strengthen asset pricing models? Moderating effects in the Fama-French framework on ESG leaders - Maulana, Yasir; Nugraha, Nugraha; Disman, Disman; Sari, Maya (Master of Management, Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2026)
This research investigates the moderating role of environmental, social, and governance (ESG) risk ratings in the relationship between traditional Fama-French framework and excess stock returns among companies listed in the ESG Leaders Index for the 2021–2023 period. Using moderated regression analysis (MRA), the findings reveal that small minus big (SMB) exerts a significant positive impact on excess returns, confirming the relevance of firm size as a pricing factor even within the sustainability-focused investment universe. Meanwhile, market risk and high minus low (HML) do not show demonstrate statistical relevance direct effects, although HML is marginally significant. Furthermore, ESG risk rating demonstrates a moderating effect only in the relationship between HML and excess returns, suggesting that sustainability considerations may weaken the traditional value premium. These results highlight the partial integration of ESG risk into asset pricing dynamics and underline the essentiality of incorporating ESG factors in developing more robust, sustainable investment strategies. The study provides practical insights for market participants, fund managers, and authorities navigating the transition toward sustainable finance in emerging markets.